Effect of autoclaving process on trueness and qualitative marginal fit of intraoral scan body manufactured from two materials: An in vitro study - Fábio Henrique de Paulo Costa Santos; Patrícia Santos de Melo; Paulo Sergio Borella; Flávio Domingues das Neves; Karla Zancope (PLoS ONE, 2025)
Statement of the problem It is not clear the effect of multiple autoclaving processes on the accuracy of scan bodies. Autoclaving dental disposables enables reuse, reducing the environmental impact of raw materials and waste. Purpose This in vitro laboratory study evaluated the effect of the autoclaving process on the intraoral scan body (SB) manufactured from different materials (Titanium and PEEK), positioned at the implant and abutment levels. Methods Two models, each with 10 implants, were created to evaluate scan body trueness made of two materials (Titanium and PEEK), and implant junction positioned at two levels (implant and abutment levels). Analyses were conducted at five distinct time points: T0 (control group with new SB), T1 (after one autoclaving cycle), T2 (10 cycles), T3 (50 cycles), and T4 (100 cycles). Forty SBs were divided into four groups (n = 10), fixed on the models according to the initial positioning, using the recommended torque, and scanned 10 times using an intraoral Sccaner (InEOS X5 scanner, Dentsply Sirona). The surface deviation was evaluated by .STL mesh overlay using an image software (Geomagic Control X software). Microscopic analyses of marginal adaptation were performed simultaneously with the digital analysis using an optical microscope (Mitutoyo™-500 Optical Microscope) with 40x magnification at four places (mesial, distal, buccal, and lingual). Statistical analysis was performed using statistical software (SPSS 29.0 software), with α = 0,05. Data were subjected to the Shapiro-Wilk normality test. To assess spatial variation after the cycles, Repeated Measures ANOVA with Bonferroni correction was used. For microscopic qualitative analysis, percentile was used to check the prevalence of clinically adapted and misfitting faces. Results Statistically significant differences in mesh deformation were detected, with PEEK SB showing greater deformation compared to Titanium, especially at the abutment level, after 100 cycles (P < 0.01). Microscopic analysis revealed that 100% of the faces were classified as “Clinically Adapted” by the three calibrated evaluators (KAPPA > 0.08). Conclusions Titanium scan bodies showed less surface deviation than PEEK but both remained below 50 µm. Internal-junction scan bodies were more affected than abutment-level ones. All scan bodies stayed within acceptable limits and viable after 100 autoclaving cycles.